Analysis of Job Promotion and Job Rotation on Employee Performance at Bank Syariah Indonesia Karawang - Hilwa Syafira Barkah; Sari Marliani; July Juliawaty (PT. Berkah Digital Teknologi, 2025)
Purpose: This study aims to analyze the impact of promotion and work rotation on employee performance at Bank Syariah Indonesia Karawang Research Methodology: Using qualitative descriptive methods, the research involved interviews, observation, and documentation, with a total of three respondents interviewed. Results: The findings reveal that promotions at Bank Syariah Indonesia Karawang are guided by the Employee Information System (SIP) and Key Performance Indicators (KPI), with a significant emphasis on employee performance and honesty. It was noted that promotions are determined by experience rather than seniority. Additionally, the job rotation system considers the length of an employee's work period; those with longer tenures are more likely to be recommended for rotation. Factors influencing this system include work duration, organizational needs, and overall performance. The study also identified differences in responsibility, adaptation to new environments, and the ability to maintain performance, all of which contribute to career advancement.. Limitations: The research is limited by a small sample size and its focus on a single location, which may impact the generalizability of the findings Contribution: This research underscores the importance of enhancing transparency and objectivity in the promotion process by strengthening the use of employee information systems and KPIs in performance evaluations.